2010
DOI: 10.1186/1471-2091-11-30
|View full text |Cite
|
Sign up to set email alerts
|

Na+-stimulated ATPase of alkaliphilic halotolerant cyanobacterium Aphanothece halophytica translocates Na+ into proteoliposomes via Na+ uniport mechanism

Abstract: BackgroundWhen cells are exposed to high salinity conditions, they develop a mechanism to extrude excess Na+ from cells to maintain the cytoplasmic Na+ concentration. Until now, the ATPase involved in Na+ transport in cyanobacteria has not been characterized. Here, the characterization of ATPase and its role in Na+ transport of alkaliphilic halotolerant Aphanothece halophytica were investigated to understand the survival mechanism of A. halophytica under high salinity conditions.ResultsThe purified enzyme cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…It is possible that these systems help Ss and Sg to survive cycles of acidification within dental plaque. Alternatively, these systems may pump Na + ions rather than H + since it has been shown that the Enterococcus hirae V-type ATPase pumps Na+ ions, and promotes survival in high pH 52 . However, the actual function of this system is still unclear and further work is required to determine the substrate specificity and physiological roles of streptococcal V type ATPases.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that these systems help Ss and Sg to survive cycles of acidification within dental plaque. Alternatively, these systems may pump Na + ions rather than H + since it has been shown that the Enterococcus hirae V-type ATPase pumps Na+ ions, and promotes survival in high pH 52 . However, the actual function of this system is still unclear and further work is required to determine the substrate specificity and physiological roles of streptococcal V type ATPases.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited information of how halotolerant ACC deaminase producing bacteria improve plant salinity resistance through altering ACC accumulation and ACO activity levels and vacuolar H + ATPase activity (Chatterjee et al 2017; Samaddar et al 2018). A previous study demonstrated that vacuolar H + ATPase activity was increased in bacteria inoculated rice plants under salt stress, which was associated with a considerable improvement in salt stress resistance (Soontharapirakkul et al 2010). Rice is a glycophyte and its salt tolerance is regulated by vacuolar H + ATPase activity (Dabbous et al 2017), which is located in the endomembrane system of the cells (Schumacher and Krebs 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This Na + active efflux occurs over a wide range of external pH (5–10), K + (0.1–300 mol m −3 ) and Na + (0.1–300 mol m −3 ). The halophilic, alkalophilic cyanobacterium Aphanothece halophytica has a Na + -dependent F O F 1 ATP synthase which, working as an ATPase in the plasmalemma, could act in active Na + efflux (Wiangno et al ., 2007; Soontharapirakkul & Incharoensakdi, 2010; Soontharapirakkul et al ., 2011; see prediction by Mitchell, 1979). Gabbay-Azaria et al .…”
Section: Organisms With Chlorophyllsmentioning
confidence: 99%